Direct Delivery of Health Promoting β-Asp-Arg Dipeptides via Stable Co-expression of Cyanophycin and the Cyanophycinase CphE241 in Tobacco Plants - Nausch, Henrik; Dorn, Mandy; Frolov, Andrej; Hoedtke, Sandra; Wolf, Petra; Broer, Inge (Frontiers in Plant Science, 2020)
Feed supplementation with β-arginine-aspartate dipeptides (β-Asp-Arg DP) shows growth promoting effects in feeding trials with fish and might also be beneficial for pig and poultry farming. Currently, these DPs are generated from purified cyanophycin (CGP), with the help of the CGP-degrading enzyme cyanophycinase (CGPase). As alternative to an in vitro production, the DPs might be directly produced in feed crops. We already demonstrated that CGP can be produced in plastids of tobacco and potato, yielding up to 9.4% of the dry weight (DW). We also transiently co-expressed CGPases in the cytosol without degrading CGP in intact cells, while degradation occurs in the homogenized plant tissue. However, transient co-expression is not feasible for field-grown CGP plants, which is necessary for bulk production. In the present study, we proved that stable co-expression of the CGPase CphE241 in CGP-producing tobacco is sufficient to degrade 2.0% CGP/DW nearly completely within 3 hours after homogenization of the leaves. In intact senescing leaves, CGP is partially released to the cytosol and degraded into DPs which limits the overall accumulation of CGP but not the level of the stable DPs. Even after 48 h, 54 µmol β-Asp-Arg DP/g DW could be detected in the extract, which correspond to 1.5% DP/DW and represents 84% of the expected amount. Thus, we developed a system for the production of β-Asp-Arg DP in field-grown plants.